Silicon monoxide composite negative electrode material and preparation method and application thereof

By using a composite negative electrode material with silicon oxide and metal doped elements embedded in the porous zeolite skeleton containing carbon nanolayers in lithium-ion batteries, the problems of volume expansion and poor conductivity of the silicon oxide negative electrode material are solved, and the performance of the battery is significantly improved.

CN119695133APending Publication Date: 2025-03-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311237832.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The silicon oxide negative electrode materials used in existing lithium-ion batteries have problems such as large volume expansion, poor conductivity, low first-time Coulomb efficiency and poor cycle life.

Method used

Through solid-phase synthesis method or chemical vapor deposition method, silicon oxide and metal doping elements are uniformly embedded in the pores of porous zeolites by using porous zeolites as the framework, and silicon oxide and metal doping elements are uniformly distributed in the pores of porous zeolites to prepare silicon oxide composite anode material.

Benefits of technology

Improves the volume expansion of lithium-ion batteries, improves conductive performance, first-week Coulomb efficiency and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695133A_ABST
    Figure CN119695133A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon monoxide composite negative electrode material as well as a preparation method and application thereof. The silicon monoxide composite negative electrode material comprises porous zeolite containing a carbon nano layer, and silicon monoxide and metal doping elements dispersed in pores of the porous zeolite, wherein the metal doping element comprises any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni and Cu elements; the mass of the metal doping element accounts for 0.3%-20% of the total mass of the silicon monoxide composite negative electrode material; the mass sum of the silicon monoxide and the metal doping element accounts for 30-70% of the total mass of the silicon monoxide composite negative electrode material; the mass of the porous zeolite containing the carbon nano layer accounts for 20-60% of the total mass of the silicon monoxide composite negative electrode material; when the silicon monoxide composite negative electrode material is applied to the lithium ion battery, the first-cycle coulombic efficiency, the reversible capacity and the cycle performance of the lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a silicon oxide composite negative electrode material and a preparation method and application thereof. Background Art

[0002] At present, the commercial negative electrode material graphite capacity can reach 365mAh / g, which is very close to its theoretical specific capacity of 372mAh / g. Therefore, if you want to further improve the energy density of the battery cell, the negative electrode material is a good entry point. Silicon-based materials are regarded as one of the most promising negative electrode materials due to their high theoretical specific capacity, low cost and environmental friendliness. However, during the process of lithium insertion and extraction, silicon-based materials will produce a large volume expansion, resulting in the crushing of silicon particles and the destruction of the electrode structure. Therefore, it is necessary to modify silicon-based materials.

[0003] Among them, silicon oxide materials have higher gram capacity and better cycle life, and are considered to have broad application prospects. However, silicon oxide also has a volume expansion of about 160%, and faces the problems of first coulomb efficiency, low conductivity and poor cycle life. Summary of the invention

[0004] The embodiment of the present invention provides a silicon oxide composite negative electrode material and a preparation method and application thereof, with the aim of solving the problems of large volume expansion rate, poor conductivity, low first coulombic efficiency and poor cycle life existing in lithium ion batteries using the existing silicon oxide negative electrode material; the present invention uses a porous zeolite containing a carbon nanolayer as a skeleton by solid phase synthesis or chemical vapor deposition, and evenly embeds silicon oxide and metal doping elements in the pores of the porous zeolite to obtain a silicon oxide composite negative electrode material; the silicon oxide composite negative electrode material provided by the embodiment of the present invention is applied to a lithium ion battery, relying on the skeleton structure of the porous zeolite, the good conductivity of the carbon nanolayer and the synergistic effect of the metal doping elements, to improve the volume expansion of the lithium ion battery, and improve the conductivity, first cycle coulombic efficiency and cycle performance of the lithium ion battery.

[0005] To this end, in a first aspect, an embodiment of the present invention provides a silicon oxide composite negative electrode material, the silicon oxide composite negative electrode material comprising: a porous zeolite containing a carbon nanolayer, and silicon oxide and a metal doping element dispersed in the pores of the porous zeolite;

[0006] wherein the carbon nanolayer is formed in the pores of the porous zeolite by deposition of a carbon source gas;

[0007] The metal doping element includes: any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu;

[0008] The mass of the metal doping element accounts for 0.3%-20% of the total mass of the silicon oxide composite negative electrode material;

[0009] The sum of the mass of the silicon oxide and the metal doping element accounts for 30%-70% of the total mass of the silicon oxide composite negative electrode material;

[0010] The mass of the porous zeolite containing the carbon nano-layer accounts for 20%-60% of the total mass of the silicon oxide composite negative electrode material.

[0011] Preferably, the porous zeolite includes: any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; the thickness of the carbon nanolayer of the porous zeolite is 1nm-60nm;

[0012] The particle size Dv50 of the porous zeolite is between 200nm and 100μm; the pore size of the porous zeolite is between 0.1nm and 10μm; and the porosity of the porous zeolite is between 25% and 90%.

[0013] Preferably, the silicon 2 oxide composite negative electrode material further comprises a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the silicon 2 oxide composite negative electrode material.

[0014] In a second aspect, an embodiment of the present invention provides a method for preparing the silicon 2 Oxide composite negative electrode material described in the first aspect, wherein the preparation method is a solid phase method, comprising:

[0015] The porous zeolite is placed in a vacuum high-temperature furnace, and a carbon source gas is introduced under a protective atmosphere and deposited in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer;

[0016] Placing a porous zeolite containing a carbon nanolayer, silicon dioxide and a material containing a metal doping element in a ball mill, and performing ball milling under a protective atmosphere, so that silicon dioxide and the material containing a metal doping element are dispersed in the pores of the porous zeolite, to obtain a precursor material;

[0017] Placing the precursor material in a tubular heating furnace and calcining it in a protective atmosphere to obtain a sintered material;

[0018] The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material.

[0019] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere;

[0020] The porous zeolite includes any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite;

[0021] The carbon source gas includes: one or more of methane, ethane, ethylene, propane, propylene, acetylene, and natural gas;

[0022] The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu elements;

[0023] The mass ratio of the porous zeolite containing the carbon nanolayer, silicon oxide and the material containing the metal doping element is [1-5]:[2-6]:[0.1-0.7].

[0024] Preferably, the ball milling speed is 200r / min-1500r / min, and the ball milling time is 8 hours-64 hours;

[0025] The calcination treatment conditions are as follows: heating to 650°C-950°C, keeping the temperature for 2 hours-8 hours, and heating rate of 3°C / min-5°C / min;

[0026] The preparation method further comprises: carbon coating the silicon monoxide composite negative electrode material;

[0027] The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating;

[0028] The mass of the carbon coating layer accounts for 0-20% of the total mass of the high-performance silicon-oxygen-silicon-oxide composite negative electrode material.

[0029] In a third aspect, an embodiment of the present invention provides a method for preparing the silicon 2 Oxide composite negative electrode material described in the first aspect, wherein the preparation method is a vapor deposition method, comprising:

[0030] The porous zeolite is placed in a vacuum high-temperature furnace, and a carbon source gas is introduced under a protective atmosphere and deposited in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer;

[0031] Placing a mixture of silicon powder, silicon dioxide powder and a material containing a metal doping element in a vacuum high-temperature furnace, heating and raising the temperature under reduced pressure until the mixture is gasified to obtain a mixed gas;

[0032] depositing the mixed gas in the pores of a porous zeolite containing a carbon nanolayer to obtain a precursor;

[0033] The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material.

[0034] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere;

[0035] The porous zeolite includes any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite;

[0036] The carbon source gas includes: one or more of methane, ethane, ethylene, propane, propylene, acetylene, and natural gas;

[0037] The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu elements;

[0038] The mass ratio of the silicon powder, silicon dioxide powder and the material containing the metal doping element is [2-5]:[1-6]:[0.1-0.7].

[0039] Preferably, the decompression conditions are as follows: vacuuming to 1Pa-250Pa, and heating at a temperature of 900°C-1400°C;

[0040] The preparation method further comprises: carbon coating the silicon monoxide composite negative electrode material;

[0041] The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating;

[0042] The mass of the carbon coating layer accounts for 0-20% of the total mass of the silicon 2 oxide composite negative electrode material.

[0043] In a fourth aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the silicon 2 Oxide composite negative electrode material described in the first aspect above.

[0044] In a fifth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate described in the fourth aspect.

[0045] An embodiment of the present invention provides a method for preparing a silicon oxide composite negative electrode material. Through a solid phase synthesis method or a chemical vapor deposition method, a porous zeolite containing a carbon nanolayer is used as a skeleton, and silicon oxide and metal doping elements are evenly embedded and distributed in the pores of the porous zeolite to obtain a silicon oxide composite negative electrode material. The preparation method provided by the present invention is simple to operate, low in cost, and easy to scale up for production.

[0046] The silicon dioxide composite negative electrode material provided in the embodiment of the present invention has, on the one hand, a porous zeolite with good mechanical strength, which can effectively withstand the volume expansion of silicon dioxide during the cycle and ensure the integrity of the material and the electrode structure, and the carbon nanolayer deposited inside the porous zeolite can effectively improve the conductivity of the negative electrode material; in addition, the doped metal elements can, on the one hand, form metal silicon oxide with the silicon dioxide in the silicon dioxide material, reduce the consumption of lithium, and improve the first coulombic efficiency of the battery; on the other hand, the formed inert metal silicon oxide can inhibit the volume expansion of silicon dioxide and improve the cycle stability.

[0047] The silicon monoxide composite negative electrode material provided in the embodiment of the present invention is applied to lithium-ion batteries, relying on the skeleton structure of pore zeolite, the good conductivity of the carbon nanolayer and the synergistic effect of metal doping elements to improve the volume expansion of lithium-ion batteries, and improve the conductivity, first-cycle coulomb efficiency and cycle performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0049] Figure 1 It is a flow chart of preparing silicon 2 Oxide composite negative electrode material by solid phase method provided by an embodiment of the present invention.

[0050] Figure 2 The present invention provides a flow chart of preparing silicon 2 Oxide composite negative electrode material by vapor deposition method.

[0051] Figure 3 It is a schematic diagram of the cross-sectional structure of the silicon monoxide composite negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0052] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0053] An embodiment of the present invention provides a silicon oxide composite negative electrode material, which includes: a porous zeolite containing a carbon nanolayer, and silicon oxide and a metal doping element dispersed in the pores of the porous zeolite.

[0054] Among them, the porous zeolite includes: any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; the particle size Dv50 of the porous zeolite is between 200nm-100μm; the pore size of the porous zeolite is between 0.1nm-10μm; the porosity of the porous zeolite is between 25%-90%; the carbon nanolayer is formed in the pores of the porous zeolite by depositing carbon source gas, and the thickness of the carbon nanolayer of the porous zeolite is between 1nm-60nm, preferably 5nm-35nm; the mass of the porous zeolite containing the carbon nanolayer accounts for 20%-60% of the total mass of the silicon oxide composite negative electrode material.

[0055] The metal doping elements include: any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu elements, which are dispersed in the pores of the porous zeolite in the form of particles; the mass of the metal doping elements accounts for 0.3%-20% of the total mass of the silicon oxide composite negative electrode material.

[0056] Silicon oxide is dispersed in the pores of porous zeolite in the form of particles, and the mass of silicon oxide and metal doping elements accounts for 30%-70% of the total mass of the silicon oxide composite negative electrode material; the chemical formula of the silicon oxide particles of the present invention is SiO x , where 0≤x≤2.

[0057] In an optional solution, the silicon 2 O composite negative electrode material provided in the embodiment of the present invention further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the silicon 2 O composite negative electrode material, preferably 15%.

[0058] The embodiments of the present invention provide two methods for preparing the silicon 2 Oxide composite negative electrode material, including a solid phase method and a vapor phase deposition method.

[0059] When the preparation method provided by the embodiment of the present invention is a solid phase method, it specifically comprises the following steps:

[0060] Step 110, placing the porous zeolite in a vacuum high-temperature furnace, introducing a carbon source gas under a protective atmosphere and depositing the carbon source gas in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer;

[0061] The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; the porous zeolite includes any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; the particle size Dv50 of the porous zeolite is between 200nm and 100μm; the pore size of the porous zeolite is between 0.1nm and 10μm; the porosity of the porous zeolite is between 25% and 90%;

[0062] The carbon source gas includes one or more of methane, ethane, ethylene, propane, propylene, acetylene and natural gas.

[0063] Step 120, placing the porous zeolite containing the carbon nanolayer, silicon dioxide and the material containing the metal doping element in a ball mill, and performing ball milling under a protective atmosphere, so that the silicon dioxide and the material containing the metal doping element are dispersed in the pores of the porous zeolite, to obtain a precursor material;

[0064] The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu;

[0065] The mass ratio of the porous zeolite containing the carbon nanolayer, silicon oxide and the material containing the metal doping element is [1-5]:[2-6]:[0.1-0.7];

[0066] The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; the rotation speed of the ball mill is 200 r / min-1500 r / min, and the ball milling time is 8 hours-64 hours.

[0067] Step 130, placing the precursor material in a tubular heating furnace and calcining it under a protective atmosphere to obtain a sintered material;

[0068] The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; the calcination treatment conditions are specifically as follows: heating to 650°C-950°C, keeping warm for 2 hours-8 hours, and a heating rate of 3°C / min-5°C / min.

[0069] Step 140, crushing, screening and demagnetizing the sintered material to obtain a silicon oxide composite negative electrode material;

[0070] Specifically, the crushing, screening and demagnetization in this step are all conventional methods, and the particle size Dv50 of the obtained silicon 2 oxide composite negative electrode material is between 100nm-200μm.

[0071] When the preparation method provided by the embodiment of the present invention is a vapor deposition method, it specifically includes the following steps:

[0072] Step 210, placing the porous zeolite in a vacuum high-temperature furnace, introducing a carbon source gas under a protective atmosphere and depositing the carbon source gas in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer;

[0073] Wherein, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere;

[0074] The porous zeolite includes: any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; the particle size Dv50 of the porous zeolite is between 200nm and 100μm; the pore size of the porous zeolite is between 0.1nm and 10μm; the porosity of the porous zeolite is between 25% and 90%;

[0075] The carbon source gas includes one or more of methane, ethane, ethylene, propane, propylene, acetylene and natural gas.

[0076] Step 220, placing a mixed material of silicon powder, silicon dioxide powder and a material containing a metal doping element in a vacuum high-temperature furnace, and heating the mixed material under reduced pressure until the mixed material is gasified to obtain a mixed gas;

[0077] The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu;

[0078] The mass ratio of silicon powder, silicon dioxide powder and material containing metal doping elements is [2-5]:[1-6]:[0.1-0.7];

[0079] The decompression conditions are specifically: vacuuming to 1Pa-250Pa, and heating temperature is 900℃-1400℃.

[0080] Step 230, depositing the mixed gas in the pores of the porous zeolite containing the carbon nanolayer to obtain a precursor;

[0081] Specifically, the mixed gas can be introduced into a deposition chamber containing a porous zeolite containing a carbon nanolayer through a carrier gas such as argon or nitrogen, or the mixed gas can be directly introduced into the deposition chamber, so that the mixed gas is deposited in the pores of the porous zeolite containing the carbon nanolayer, and nucleates and grows to form silicon dioxide particles and metal element particles in the pores.

[0082] Step 240, crushing, screening and demagnetizing the precursor to obtain a silicon oxide composite negative electrode material;

[0083] Specifically, the crushing, screening and demagnetization in this step are all conventional methods, and the particle size Dv50 of the obtained silicon 2 oxide composite negative electrode material is between 100nm-200μm.

[0084] The present invention provides the above-mentioned silicon dioxide composite negative electrode material prepared by the preparation method, and its structural schematic diagram is as follows: Figure 3 As shown, it can be seen that the porous zeolite containing the carbon nanolayer serves as a framework structure, and silicon dioxide and metal elements are dispersed in the pores of the porous zeolite in a particle state.

[0085] In an optional solution, the above two methods for preparing silicon monoxide composite negative electrode materials further include: carbon coating the silicon monoxide composite negative electrode material.

[0086] The carbon coating method includes: gas phase coating, liquid phase coating or solid phase coating;

[0087] The mass of the formed carbon coating layer accounts for 0-20% of the total mass of the silicon oxide composite negative electrode material.

[0088] The silicon 2 Oxide composite negative electrode material or the silicon 2 Oxide composite negative electrode material containing a carbon coating layer provided in the embodiment of the present invention can be used as a negative electrode active material together with a conductive agent and a binder to prepare a negative electrode sheet.

[0089] The negative electrode sheet containing the silicon oxide composite negative electrode material or the silicon oxide composite negative electrode material containing a carbon coating layer can be assembled with the positive electrode sheet, electrolyte / solid electrolyte, and separator into a lithium ion battery.

[0090] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon 2 Oxide composite negative electrode material of the present invention are respectively described below with multiple specific examples.

[0091] Example 1

[0092] This embodiment provides a process for preparing a silicon 2 Oxide composite negative electrode material by a solid phase method and a performance test. The specific preparation process is as follows.

[0093] (1) 2 kg of clinoptilolite was placed in a vacuum high-temperature furnace, heated to 1000° C. in an argon atmosphere, and acetylene gas was introduced for 20 seconds to form a clinoptilolite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 5 nm; wherein the particle size Dv50 of the clinoptilolite was 500 nm, the average pore size was 30 nm, and the porosity was 75%.

[0094] (2) 1 kg of clinoptilolite containing a carbon nanolayer, 2 kg of silicon dioxide and 120 g of aluminum oxide were placed in a ball mill. Under an argon atmosphere, the speed was set to 800 r / min and the ball milling time was set to 24 hours to disperse silicon dioxide and aluminum oxide in the pores of the clinoptilolite to obtain a precursor material.

[0095] (3) The precursor material is placed in a tubular heating furnace, heated to 900° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept at this temperature for 2 hours to obtain a sintered material.

[0096] (4) The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Al accounts for 4% of the total mass of the silicon oxide composite negative electrode material.

[0097] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is placed in a rotary kiln, the temperature is raised to 800°C under an argon atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 2:1 for gas phase coating, the gas source is turned off after keeping the temperature for 100 minutes, and the material is discharged and classified after cooling to room temperature to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0098] The silicon 2 Oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode pole piece and assembled into a button-type half-cell for testing. The specific process is as follows.

[0099] The preparation method of the button half-cell is as follows: the silicon oxide composite negative electrode material containing a carbon coating layer, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 95%:2%:3%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.

[0100] The button half-cell was assembled in a glove box filled with argon atmosphere, using metallic lithium as the counter electrode and 1 mol / L LiPF 6 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC to DEC is 1:1) was used as the electrolyte to assemble a half-cell. A charge-discharge instrument was used to perform constant current charge-discharge mode tests, with a discharge cut-off voltage of 0.005V and a charge cut-off voltage of 2V. The first week of charge-discharge tests was performed at a current density of 0.1C, and subsequent cycles were performed at a current density of 3C.

[0101] The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate after 300 and 600 cycles of the button-type half-cell prepared in this embodiment are shown in Table 1.

[0102] Example 2

[0103] This embodiment provides a process for preparing a silicon 2 Oxide composite negative electrode material by a solid phase method and a performance test. The specific preparation process is as follows.

[0104] (1) 3 kg of mordenite was placed in a vacuum high-temperature furnace, heated to 1000° C. in an argon atmosphere, and acetylene gas was introduced for 30 seconds to form mordenite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 7 nm; wherein the particle size Dv50 of the mordenite was 400 nm, the average pore size was 50 nm, and the porosity was 70%.

[0105] (2) 2 kg of mordenite containing a carbon nanolayer, 4 kg of silicon dioxide, and 300 g of magnesium oxide were placed in a ball mill. Under an argon atmosphere, the speed was set to 900 r / min and the ball milling time was set to 18 hours to disperse silicon dioxide and magnesium oxide in the pores of the mordenite to obtain a precursor material.

[0106] (3) The precursor material is placed in a tubular heating furnace, heated to 950° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept at this temperature for 2 hours to obtain a sintered material.

[0107] (4) The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Mg accounts for 5% of the total mass of the silicon oxide composite negative electrode material.

[0108] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is placed in a rotary kiln, the temperature is raised to 800°C under an argon atmosphere, argon and natural gas are introduced in a volume ratio of 3:2 for gas phase coating, the gas source is turned off after keeping warm for 90 minutes, and the material is discharged and classified after cooling to room temperature to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0109] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0110] Example 3

[0111] This embodiment provides a process for preparing a silicon 2 Oxide composite negative electrode material by a solid phase method and a performance test. The specific preparation process is as follows.

[0112] (1) 3 kg of erionite was placed in a vacuum high-temperature furnace, heated to 1000° C. in an argon atmosphere, and acetylene gas was introduced for 25 seconds to form erionite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 6 nm; wherein the particle size Dv50 of the erionite was 1 μm, the average pore size was 200 nm, and the porosity was 50%.

[0113] (2) 1.5 kg of erionite containing a carbon nanolayer, 3 kg of silicon dioxide, and 250 g of zinc oxide were placed in a ball mill. Under an argon atmosphere, the rotation speed was set to 1000 r / min and the ball milling time was set to 16 hours to disperse silicon dioxide and zinc oxide in the pores of the erionite to obtain a precursor material.

[0114] (3) The precursor material is placed in a tubular heating furnace, heated to 950° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept at this temperature for 3 hours to obtain a sintered material.

[0115] (4) The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Zn accounts for 5.6% of the total mass of the silicon oxide composite negative electrode material.

[0116] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is mixed with asphalt emulsion in a mass ratio of 20:1, stirred for 10 hours to form a uniform slurry, the slurry is dried and placed in a rotary kiln, heated to 950°C under a protective atmosphere and kept warm for 80 minutes, cooled, discharged and classified to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0117] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0118] Example 4

[0119] This embodiment provides a process for preparing a silicon 2 Oxide composite negative electrode material by a solid phase method and a performance test. The specific preparation process is as follows.

[0120] (1) 5 kg of zeolite was placed in a vacuum high-temperature furnace, heated to 1000°C in an argon atmosphere, and acetylene gas was introduced for 25 seconds to form zeolite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 6 nm; wherein the particle size Dv50 of the zeolite was 2 μm, the average pore size was 400 nm, and the porosity was 82%.

[0121] (2) 3 kg of zeolite containing a carbon nanolayer, 6 kg of silicon oxide and 500 g of magnesium chloride were placed in a ball mill. Under an argon atmosphere, the speed was set to 1500 r / min and the ball milling time was set to 10 hours to disperse silicon oxide and magnesium chloride in the pores of the zeolite to obtain a precursor material.

[0122] (3) The precursor material is placed in a tubular heating furnace, heated to 1000° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept at this temperature for 3 hours to obtain a sintered material.

[0123] (4) The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Mg accounts for 5.6% of the total mass of the silicon oxide composite negative electrode material.

[0124] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material and graphene are dissolved in ethanol at a ratio of 19:1, and stirred for 7 hours to make the slurry uniform; then the slurry is dried, placed in a rotary kiln, heated to 900°C in a protective atmosphere and kept warm for 4 hours, cooled, discharged, and classified to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0125] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0126] Example 5

[0127] This embodiment provides a process for preparing a silicon oxide composite negative electrode material by chemical vapor deposition and a performance test. The specific preparation process is as follows.

[0128] (1) 3 kg of zeolite was placed in a vacuum high-temperature furnace, heated to 1000°C in an argon atmosphere, and acetylene gas was introduced for 30 seconds to form zeolite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 6 nm; wherein the particle size Dv50 of the zeolite was 30 μm, the average pore size was 700 nm, and the porosity was 58%.

[0129] (2) A mixture of 3 kg of silicon powder, 1.5 kg of silicon dioxide powder, and 200 g of lithium hydride was placed in a vacuum high-temperature furnace, evacuated to 10 Pa, heated to 1100° C., and kept warm for 3 hours until the mixture was vaporized to obtain a mixed gas.

[0130] (3) The mixed gas is introduced into a deposition chamber containing 1.5 kg of stilbite containing a carbon nanolayer through a carrier gas, argon gas, so that the mixed gas is deposited in the pores of the stilbite containing the carbon nanolayer to obtain a precursor.

[0131] (4) The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Li accounts for 4.4% of the total mass of the silicon oxide composite negative electrode material.

[0132] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is mixed with petroleum asphalt in a mass ratio of 16:1, placed in a rotary kiln, kept at 950°C for 150 minutes under a protective atmosphere, cooled to room temperature, and then discharged and classified to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0133] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0134] Example 6

[0135] This embodiment provides a process for preparing a silicon oxide composite negative electrode material by chemical vapor deposition and a performance test. The specific preparation process is as follows.

[0136] (1) 2 kg of zeolite was placed in a vacuum high-temperature furnace, heated to 1000°C in an argon atmosphere, and acetylene gas was introduced for 20 seconds to form zeolite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 5 nm; wherein the particle size Dv50 of the zeolite was 60 μm, the average pore size was 2 μm, and the porosity was 45%.

[0137] (2) A mixture of 2 kg of silicon powder, 1 kg of silicon dioxide powder, and 150 g of magnesium chloride is placed in a vacuum high-temperature furnace, evacuated to 50 Pa, heated to 1000° C., and kept warm for 4 hours until the mixture is vaporized to obtain a mixed gas.

[0138] (3) The mixed gas is introduced into a deposition chamber containing 1.5 kg of stilbite containing a carbon nanolayer through a carrier gas, argon gas, so that the mixed gas is deposited in the pores of the stilbite containing the carbon nanolayer to obtain a precursor.

[0139] (4) The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Mg accounts for 5% of the total mass of the silicon oxide composite negative electrode material.

[0140] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material and phenolic resin are dissolved in tetrahydrofuran at a ratio of 15:1, stirred for 8 hours to form a uniform slurry and then directly dried, placed in a rotary kiln, heated to 900°C in a protective atmosphere and kept warm for 2 hours, cooled, discharged and classified to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0141] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0142] Example 7

[0143] This embodiment provides a process for preparing a silicon oxide composite negative electrode material by chemical vapor deposition and a performance test. The specific preparation process is as follows.

[0144] (1) 3.5 kg of mordenite was placed in a vacuum high-temperature furnace, heated to 1000° C. in an argon atmosphere, and acetylene gas was introduced for 30 seconds to form mordenite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 7 nm; wherein the particle size Dv50 of the mordenite was 85 μm, the average pore size was 5 μm, and the porosity was 63%.

[0145] (2) A mixture of 3 kg of silicon powder, 4 kg of silicon dioxide powder, and 350 g of molybdenum oxide was placed in a vacuum high-temperature furnace, evacuated to 100 Pa, heated to 1050° C., and kept warm for 3 hours until the mixture was vaporized to obtain a mixed gas.

[0146] (3) introducing the mixed gas into a deposition chamber containing stilbene containing the carbon nanolayer through carrier gas argon, so that the mixed gas is deposited in the pores of the stilbene containing the carbon nanolayer to obtain a precursor.

[0147] (4) The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Mo accounts for 5% of the total mass of the silicon oxide composite negative electrode material.

[0148] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is placed in a rotary kiln, heated to 950°C under a protective atmosphere, and a mixed gas of argon and natural gas and ethylene is introduced in a volume ratio of 4:3 for gas phase coating, wherein the volume ratio of natural gas to ethylene is 1:1. After keeping warm for 100 minutes, the gas source is turned off, and the material is discharged and classified after cooling to room temperature to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0149] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0150] Example 8

[0151] This embodiment provides a process for preparing a silicon oxide composite negative electrode material by chemical vapor deposition and a performance test. The specific preparation process is as follows.

[0152] (1) 5 kg of zeolite was placed in a vacuum high-temperature furnace, heated to 1000°C in an argon atmosphere, and acetylene gas was introduced for 25 seconds to form zeolite with a carbon nanolayer deposited in the pores, wherein the thickness of the carbon nanolayer was 6 nm; wherein the particle size Dv50 of the zeolite was 100 μm, the average pore size was 6 μm, and the porosity was 68%.

[0153] (2) A mixture of 3 kg of silicon powder, 1.5 kg of silicon dioxide powder, and 200 g of lithium hydride was placed in a vacuum high-temperature furnace, evacuated to 10 Pa, heated to 1100° C., and kept warm for 3 hours until the mixture was vaporized to obtain a mixed gas.

[0154] (3) The mixed gas is introduced into a deposition chamber containing zeolite containing a carbon nanolayer through a carrier gas argon gas, so that the mixed gas is deposited in the pores of the porous zeolite containing the carbon nanolayer to obtain a precursor.

[0155] (4) The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material, wherein the mass of the metal doping element Li accounts for 4.4% of the total mass of the silicon oxide composite negative electrode material.

[0156] The prepared silicon oxide composite negative electrode material is carbon-coated: 1 kg of silicon oxide composite negative electrode material is mixed with petroleum asphalt in a mass ratio of 16:1, placed in a rotary kiln, kept at 950°C for 150 minutes under a protective atmosphere, cooled to room temperature, and then discharged and classified to obtain a silicon oxide composite negative electrode material containing a carbon coating layer.

[0157] The silicon oxide composite negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode plate and assembled into a button half-cell for testing. The specific process was the same as in Example 1. The test data of the first cycle coulombic efficiency, reversible capacity, and capacity retention rate of the button half-cell after 300 and 600 cycles are shown in Table 1.

[0158] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.

[0159] Comparative Example 1

[0160] This comparative example provides a preparation method and performance test of a traditional silicon monoxide negative electrode material, and the specific preparation process is as follows.

[0161] (1) 1 kg of silicon powder and 2 kg of silicon dioxide powder were mixed evenly, placed in a vacuum high-temperature furnace, evacuated to 200 Pa, heated to 1600° C., and kept warm for 3 hours to obtain a mixed gas.

[0162] (2) Cooling the mixed gas and depositing it on a substrate to obtain a precursor.

[0163] (3) After the precursor is crushed, screened, and demagnetized, a traditional silicon oxide negative electrode material is obtained.

[0164] The prepared traditional silicon oxide negative electrode material is carbon-coated: 1 kg of traditional silicon oxide negative electrode material is mixed with asphalt emulsion in a mass ratio of 18:1, stirred for 9 hours to form a uniform slurry, the slurry is dried and placed in a rotary kiln, heated to 1000°C under a protective atmosphere and kept warm for 90 minutes, cooled, discharged and classified to obtain a traditional silicon oxide negative electrode material containing a carbon coating layer.

[0165] The negative electrode sheet was prepared using the conventional silicon oxide negative electrode material containing a carbon coating layer prepared in this comparative example and assembled into a button-type half-cell for testing. The specific process was the same as in Example 1. The test data is detailed in Table 1.

[0166] Comparative Example 2

[0167] This comparative example provides a preparation method and performance test of a silicon monoxide negative electrode material, which is different from the embodiment in that no metal doping is performed. The specific preparation process is as follows.

[0168] (1) 1 kg of silicon powder and 2 kg of silicon dioxide powder were mixed evenly, placed in a vacuum high-temperature furnace, evacuated to 200 Pa, heated to 1600° C., and kept warm for 3 hours to obtain a mixed gas.

[0169] (2) The mixed gas is cooled and deposited in the pores of 1 kg of mordenite to obtain a precursor.

[0170] (3) The precursor is crushed, screened, and demagnetized to obtain a silicon oxide negative electrode material that is not doped with metal elements.

[0171] The prepared silicon oxide negative electrode material is carbon-coated: 1 kg of silicon oxide negative electrode material is placed in a rotary kiln, heated to 950°C under a protective atmosphere, and a mixed gas of argon and natural gas and ethylene is introduced in a volume ratio of 4:3 for gas phase coating, wherein the volume ratio of natural gas to ethylene is 1:1. After keeping warm for 100 minutes, the gas source is turned off, and the material is discharged and classified after cooling to room temperature to obtain a silicon oxide negative electrode material containing a carbon coating layer.

[0172] The silicon 2 Oxide negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare a negative electrode sheet and assembled into a button-type half-cell for testing. The specific process was the same as in Example 1. The test data is detailed in Table 1.

[0173] Table 1 shows the first-week coulombic efficiency, reversible capacity and cycle retention rate of the button-type half-cells assembled in Examples 1-8 and Comparative Examples 1-2. The results are shown in Table 1.

[0174]

[0175] Table 1

[0176] It can be seen from the test results in Table 1 that the first coulombic efficiency of the batteries of Examples 1-8 is higher than that of the batteries of Comparative Examples 1 and 2. The reasons are as follows: on the one hand, the present invention uses a porous zeolite containing a carbon nanolayer as a skeleton structure, so that the strength of the silicon oxide inside it is improved and its expansion is inhibited, which can ensure that the material and electrode structure are not destroyed during the cycle; and the carbon nanolayer deposited inside the pores of the porous zeolite can effectively improve the electrical conductivity of the material; on the other hand, the doped metal elements can generate inert metal silicon oxide compounds with the silicon dioxide in the silicon oxide, which can not only avoid excessive consumption of the lithium source and improve the first-week coulombic efficiency, but also limit the volume expansion of silicon oxide.

[0177] It can be seen from the cycle test data that the cycle capacity retention rates of the button half-cells of Examples 1-8 after 300 and 600 cycles are greater than those of the batteries of Comparative Examples 1-2. It can also be further proved that, compared with the traditional silicon oxide negative electrode material of Comparative Example 1 and the silicon oxide negative electrode material without metal element doping of Comparative Example 2, the materials prepared in Examples 1-8 of the present invention have better structural integrity, which benefits from the skeleton structure of the porous zeolite, good conductivity and multiple effects of metal doping elements, thereby achieving low volume expansion, long cycle life and high initial efficiency of the battery.

[0178] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A silicon oxide composite negative electrode material, characterized in that: The silicon oxide composite negative electrode material comprises: a porous zeolite containing a carbon nanolayer, and silicon oxide and a metal doping element dispersed in the pores of the porous zeolite; wherein the carbon nanolayer is formed in the pores of the porous zeolite by deposition of a carbon source gas; The metal doping element includes: any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu; The mass of the metal doping element accounts for 0.3%-20% of the total mass of the silicon oxide composite negative electrode material; The sum of the mass of the silicon oxide and the metal doping element accounts for 30%-70% of the total mass of the silicon oxide composite negative electrode material; The mass of the porous zeolite containing the carbon nano-layer accounts for 20%-60% of the total mass of the silicon oxide composite negative electrode material.

2. The silicon 2 Oxide composite negative electrode material according to claim 1, characterized in that: The porous zeolite comprises: any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; the thickness of the carbon nanolayer of the porous zeolite is 1nm-60nm; The particle size Dv50 of the porous zeolite is between 200nm and 100μm; the pore size of the porous zeolite is between 0.1nm and 10μm; and the porosity of the porous zeolite is between 25% and 90%.

3. The silicon 2 Oxide composite negative electrode material according to claim 1, characterized in that: The silicon 2 oxide composite negative electrode material further comprises a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the silicon 2 oxide composite negative electrode material.

4. A method for preparing the silicon 2 Oxide composite negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method is a solid phase method, comprising: The porous zeolite is placed in a vacuum high-temperature furnace, and a carbon source gas is introduced under a protective atmosphere and deposited in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer; Placing a porous zeolite containing a carbon nanolayer, silicon dioxide and a material containing a metal doping element in a ball mill, and performing ball milling under a protective atmosphere, so that silicon dioxide and the material containing a metal doping element are dispersed in the pores of the porous zeolite, to obtain a precursor material; Placing the precursor material in a tubular heating furnace and calcining it in a protective atmosphere to obtain a sintered material; The sintered material is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material.

5. The preparation method according to claim 4, characterized in that: The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; The porous zeolite includes any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; The carbon source gas includes: one or more of methane, ethane, ethylene, propane, propylene, acetylene, and natural gas; The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu elements; The mass ratio of the porous zeolite containing the carbon nanolayer, silicon oxide and the material containing the metal doping element is [1-5]:[2-6]:[0.1-0.7].

6. The preparation method according to claim 4, characterized in that: The ball milling speed is 200r / min-1500r / min, and the ball milling time is 8 hours-64 hours; The calcination treatment conditions are as follows: heating to 650°C-950°C, keeping the temperature for 2 hours-8 hours, and heating rate of 3°C / min-5°C / min; The preparation method further comprises: carbon coating the silicon monoxide composite negative electrode material; The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating; The mass of the carbon coating layer accounts for 0-20% of the total mass of the high-performance silicon-oxygen-silicon-oxide composite negative electrode material.

7. A method for preparing the silicon 2 Oxide composite negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method is a vapor deposition method, comprising: The porous zeolite is placed in a vacuum high-temperature furnace, and a carbon source gas is introduced under a protective atmosphere and deposited in the pores of the porous zeolite to form a porous zeolite containing a carbon nanolayer; Placing a mixture of silicon powder, silicon dioxide powder and a material containing a metal doping element in a vacuum high-temperature furnace, heating and raising the temperature under reduced pressure until the mixture is gasified to obtain a mixed gas; depositing the mixed gas in the pores of a porous zeolite containing a carbon nanolayer to obtain a precursor; The precursor is crushed, screened and demagnetized to obtain a silicon oxide composite negative electrode material.

8. The preparation method according to claim 7, characterized in that: The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; The porous zeolite includes any one of clinoptilolite, mordenite, chabazite, erionite, phillipsite, and stilbite; The carbon source gas includes: one or more of methane, ethane, ethylene, propane, propylene, acetylene, and natural gas; The material containing metal doping elements includes: a compound containing any one of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, and Cu elements; The mass ratio of the silicon powder, silicon dioxide powder and the material containing the metal doping element is [2-5]:[1-6]:[0.1-0.7].

9. The preparation method according to claim 7, characterized in that: The decompression conditions are specifically: vacuuming to 1Pa-250Pa, and heating temperature is 900°C-1400°C; The preparation method further comprises: carbon coating the silicon monoxide composite negative electrode material; The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating; The mass of the carbon coating layer accounts for 0-20% of the total mass of the silicon 2 oxide composite negative electrode material.

10. A negative electrode plate, characterized in that: The negative electrode plate comprises the silicon monoxide composite negative electrode material as described in any one of claims 1 to 3.

11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 10 above.